2007
DOI: 10.1002/ijc.22681
|View full text |Cite
|
Sign up to set email alerts
|

L576P KIT mutation in anal melanomas correlates with KIT protein expression and is sensitive to specific kinase inhibition

Abstract: Activating mutations in either BRAF or NRAS are seen in a significant number of malignant melanomas, but their incidence appears to be dependent to ultraviolet light exposure. Thus, BRAF mutations have the highest incidence in non-chronic sun damaged (CSD), and are uncommon in acral, mucosal and CSD melanomas. More recently, activating KIT mutations have been described in rare cases of metastatic melanoma, without further reference to their clinical phenotypes. This finding is intriguing since KIT expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
190
1
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 228 publications
(212 citation statements)
references
References 22 publications
17
190
1
4
Order By: Relevance
“…[6][7][8][9]14,15 Most of these reported mutations are predicted to be sensitive to tyrosine kinase inhibitors. Indeed, clinical studies using imatinib in melanoma patients with confirmed KIT-activating mutations have yielded promising results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[6][7][8][9]14,15 Most of these reported mutations are predicted to be sensitive to tyrosine kinase inhibitors. Indeed, clinical studies using imatinib in melanoma patients with confirmed KIT-activating mutations have yielded promising results.…”
Section: Discussionmentioning
confidence: 99%
“…The PDGFRA gene, like KIT, is located at chromosome 4q12, which is a region that displays copy number variation in melanoma. 9 Although no PDGFRA mutations have been reported to date in melanoma, 7,9,26,27 no data are available for the ocular subtype. While we did not identify any PDGFRA mutations in exons 12 or 18, we did identify an intron 18-point mutation in one CD117-positive choroidal melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations